The Influence of Sexual Assault Resistance on Reporting Tendencies and Law Enforcement Response: Findings From the National Crime Victimization Survey - Pinciotti, Caitlin M. (Journal of interpersonal violence, 2021)
Despite its prevalence, sexual assault remains a vastly underreported crime. Previous research suggests that engagement in certain types of resistance during an assault affects the way in which both victims and others perceive the attack; such perceptions influence victims’ likelihood of reporting the assault to law enforcement as well as the criminal justice system response to reported allegations. Using a fight/flight/freeze theoretical framework, the current study sought to examine how forceful, nonforceful, and freeze responding influenced victim reporting and the extent to which reported assaults were pursued and investigated by law enforcement. Using data from the National Crime Victimization Survey between 2010 and 2016, logistic regression analysis indicated that victims are significantly less likely to report to law enforcement if they froze during the attack. Interestingly, although engagement in forceful resistance increases victims’ likelihood of reporting to law enforcement, it has no bearing on law enforcement response beyond the effect of physical injury. Rather, physical injury (e.g., bruises, cuts, broken bones) is the only predictor of law enforcement response to sexual assault allegations. Findings suggest that whereas fight and freeze responses to sexual victimization influence victims’ willingness to report to law enforcement, resistance is not uniquely predictive of law enforcement response once physical injury is considered.